(untitled) (Yangi O’zbekiston taraqqiyotida tadqiqotlarni o’rni va rivojlanish omillari, 2025)
Abstract: The article analyzes and evaluates the importance of non-verbal communication in teaching process. Non-verbal communication is an essential aspect of human interaction, influencing how we express emotions, establish relationships, and convey meaning. Awareness of cultural variations in non-verbal communication not only helps prevent misunderstandings but also fosters respect and promotes stronger interpersonal connections.